Partisipasi Perempuan Dalam Aktivitas Komunikasi Politik Di Kabupaten Blitar - Andiwi Meifilina (KOLONI, 2024)
The world of politics is a man's world due to an image that may not be entirely accurate about political life, namely that politics is dirty, hard, full of intrigue and so on. The increase in the percentage of legislative candidates is a big concern regarding women's political abilities. Most men consider women as weak parties who are usually considered only sweeteners or cheerleaders in the world of politics. Currently, there is an increase in the number of female legislative members in the Blitar Regency DPRD from 2004, 2009, 2014 to 2019, so it can be seen that many women are entering the world of politics through legislative institutions. The aim of this study is to find out how women participate in political communication activities and the obstacles to women in politics. The method used in this study is a qualitative approach where research is used to examine natural objects where the researcher is the key instrument, data collection techniques are carried out in combination, data analysis is inductive, and the results of qualitative research emphasize meaning rather than generalization. This research discusses the role of women in national politics using a historical analysis method, an analysis based on history that has occurred. There are movements emerging that advocate equal position between men and women. Then the presence of traditional views which can be said to be very relevant places women in a position that is not worthy of being used as competitors. Currently, the position of women who can occupy seats in parliament in governments such as the DPR, DPD, MPR and DPRD is still quite lacking, even if you look at the index which is decreasing from year to year. In the future, women's involvement in the political field must continue to provide support from various groups to advance and increase the role of women so that women are more confident in accessing the political field by improving the quality of human resources with political education for women.